Use of fatty acids as dietary indicators in northern krill, , Meganyctiphanes norvegica, from northeastern Atlantic, Kattegat, and Mediterranean waters - Patti Virtue; Mayzaud, P; Albessard, E; Peter Nichols (2000)
Fatty acids of the triacylglycerol (TG) and polar lipid (PL) fractions were compared from northern krill, Meganyctiphanes norvegica, sampled in the Clyde Sea in the Atlantic, the Kattegat at the Alkor Deep, and the Ligurian Sea in the Mediterranean. Possible biotransformations of fatty acids in the food chain were examined in mixed zooplankton and krill faecal material from the Ligurian Sea and Kattegat. The Ligurian Sea population was distinguished from the Kattegat and Clyde Sea populations in terms of both TG and PL fatty acid profiles. The Kattegat and Clyde Sea populations were separated from each other in terms of their PL fatty acid profiles only. Krill sampled in winter from all sites had significantly higher levels of 20:1 and 22:1 fatty acids in the TG fraction (9–17%) than krill sampled in summer (1–10%). These fatty acids in particular indicate carnivorous dietary input, as they are found in high levels in copepods, which are the major prey species of M. norvegica. Levels of 22:6(n–3) were significantly higher than 20:5(n–3) in Ligurian krill, which, together with other specific marker fatty acids, suggested a predominance of dinoflagellates and other nondiatom species in their diet. TG fatty acids in Kattegat and Clyde Sea krill indicate a predominance of diatoms in the diet.